PENGARUH VARIASI PENGOLAHAN CANGKANG KERANG KIJING LOKAL (Pilsbryoconcha exilis Lea) TERHADAP KADAR TIMBAL (Pb) DAN KALSIUM SEBAGAI POTENSI PAKAN TERNAK UNGGAS UNTUK SUMBER BELAJAR BIOLOGI - Bagus Rachman Satrya; Agus Sutanto; Kartika Sari (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2021)
The Raman Dam area has the potential to be contaminated with heavy metals due to rice field activities, near cross-regional roads as well as tourist areas and industrial areas. This has an impact on the lead content in local deer shells. This research aims to: 1. find out the most appropriate processing variations in reducing levels of the heavy metal lead (Pb), 2. find out the most appropriate processing variations in maintaining the calcium (Ca) content of kijing shells, 3. provide information about the potential of processed kijing shells as a animal feed, 4. make research results a source of information on learning biology in the form of posters. This research used a completely randomized design (CRD) method with 4 treatments, namely, steamed shell processing (BW0), boiled (CW0), sauteed (DW0) and fresh shells as a control (AW0. To measure the metal lead and calcium content of the shells, namely using Vogel's Spectrophometer UV-Vis analysis method followed by one-way Anava analysis technique and Tukey's advanced test. Based on the analysis results, the processing treatment that reduces the lead content the most is shell processing by boiling (CW0) at 815,488 ppm, while the processing treatment that can Maintaining the highest calcium content is processing the shell by steaming (BW0) amounting to 826,775 ppm. The results of this research were also developed as a source of biological information in the form of a poster.